The Belgian Contribution to Surrealism : Edinburgh International Festival 1971. - International Festival Edinburgh 1971; Royal Scottish Academy, Edinburgh (Edinburgh : Scottish Arts Council, 1971)
Alechinsky, Pierre ; Bury, Pol ; Chemay, Jacques ; Delvaux, Paul ; Dotremont, Christian ; Folon ; Graverol, Jane ; Lacomblez, Jaques ; Landuyt, Octave ; Lefrancq, Marcel G. ; Magritte, René ; Mariën, Marcel ; Mesens, E.L.T. ; Roquet, Maurice ; Simon, Armand ; Ubac, Raoul ; Vandercam, Serge
The Belgian Contribution to Surrealism : Edinburgh International Festival 1971, at the Royal Scottish Academy, The Mound, Edinburgh, 21st August to 19th September 1971
boek